SPLUS J142445.34–254247.1: An r-process–enhanced, Actinide-boost, Extremely Metal-poor Star Observed with GHOST - Vinicius M. Placco; Felipe Almeida-Fernandes; Erika M. Holmbeck; Ian U. Roederer; Mohammad K. Mardini; Christian R. Hayes; Kim Venn; Kristin Chiboucas; Emily Deibert; Roberto Gamen; Jeong-Eun Heo; Miji Jeong; et al. (The Astrophysical Journal, 2023)
We report on a chemo-dynamical analysis of SPLUS J142445.34−254247.1 (SPLUS J1424−2542), an extremely metal-poor halo star enhanced in elements formed by the rapid neutron-capture process ( r -process). This star was first selected as a metal-poor candidate from its narrowband S-PLUS photometry and followed up spectroscopically in medium resolution with Gemini-South/GMOS, which confirmed its low-metallicity status. High-resolution spectroscopy was gathered with GHOST at Gemini-South, allowing for the determination of the chemical abundances for 36 elements, from carbon to thorium. At [Fe/H] = −3.39, SPLUS J1424−2542 is one of the lowest-metallicity stars with measured Th and has the highest $\mathrm{log}\epsilon (\mathrm{Th}/\mathrm{Eu})$ observed to date, making it part of the “actinide-boost” category of r -process–enhanced stars. The analysis presented here suggests that the gas cloud from which SPLUS J1424−2542 formed must have been enriched by at least two progenitor populations. The light-element ( Z ≤ 30) abundance pattern is consistent with the yields from a supernova explosion of metal-free stars with 11.3–13.4 M _⊙ , and the heavy-element ( Z ≥ 38) abundance pattern can be reproduced by the yields from a neutron star merger (1.66 M _⊙ and 1.27 M _⊙ ) event. A kinematical analysis also reveals that SPLUS J1424−2542 is a low-mass, old halo star with a likely in situ origin, not associated with any known early merger events in the Milky Way.